Visible light improved, photocatalytic activity of magnetically separable titania nanocomposite - Aziz, A.A.; Cheng, C.K.; Ibrahim, S.; Matheswaran, M.; Saravanan, P. (Elsevier, 2012)
A visible light improved, magnetically separable TiO 2 nanocomposite was successfully synthesized with silicon dioxide (SiO 2) as coating and supported on a permanent magnet Viz., nickel ferrite (NiFe 2O 4). Thus synthesized photocatalysts was further characterized for its crystalline phase, particle size, surface morphology, inorganic composition, adsorption-desorption hysteresis, BET surface area, pore size distribution, magnetic hysteresis, saturation magnetization, coercivity, elemental composition, chemical state, electronic state and visible light absorption spectra analysis with respective techniques. The crystallographic peak and inorganic elemental composition revealed the structure and composition of pure and nanocomposite TiO 2. The prepared titania nanocomposite resulted in lower band gap energy (2.26eV) and higher visible light absorption between 400 and 800nm than that of pure TiO 2 (2.76eV). The photocatalytic activity was investigated with a recalcitrant phenolic compound namely 2,4-dichlorophenol (2,4-DCP) as a model pollutant under direct bright and diffused sunlight irradiation. An almost complete degradation of 2,4-DCP was achieved with an initial concentration of 50mg/L for TiO 2 nanocomposite in 90min and 5h under bright and diffused sunlight conditions. Similarly pure TiO 2 resulted in a nearly complete degradation in 180min under bright and â90 in 5h under diffused conditions. Further the TiO 2 nanocomposite was recovered under a magnetic field with a mass recovery â95. The nanocomposite also exhibited improved remanence, saturation magnetization and coercivity property along with good stability against magnetic property losses for reuse. Â© 2012 Elsevier B.V.